Instrumented measurement of shoulder anterior posterior laxity - Yeap, Jun Ann (2015)
The purpose of this study was to assess the anterior-posterior translation of the glenohumeral (GH) joint using an instrumented shoulder mechanical device. Thirty-four random subjects with no history of shoulder injury and two other male subjects with history of right shoulder dislocations participated in this study. Shoulder laxity in anterior, posterior and global was obtained and unpaired student’s t-tests were performed on each category to analyze the probability of differences among the focus groups. The effect of gender, shoulder dominancy, sports activeness, basketball players, as well as history of shoulder injuries were investigated on the glenohumeral joint laxity. Results obtained in this study were analyzed and compared against previous work as well as normative data of shoulder laxity in published literature. In this study, the global glenohumeral joint translation varied from 14.00 to 29.67 mm with a mean of 21.65 ± 3.80 mm. A comparison between male and female subjects, and male dominant and non-dominant shoulders revealed statistically significant difference (p ˂ 0.05). In sports activeness group, sports active shows significant difference than sports inactive (p ˂ 0.05), but in basketball players comparison, there was no significant difference (p >0.05). In comparing healthy and injured shoulders, significant difference (p <0.05)was found. Lastly, shoulders displayed significantly more glenohumeral joint translation in the posterior direction compared to anterior direction.